Transcriptome and Co-expression Network Analyses Reveal Differential Gene Expression and Pathways in Response to Severe Drought Stress in Peanut (Arachis hypogaea L.) - Zhao, Nannan; Cui, Shunli; Li, Xiukun; Liu, Bokuan; Deng, Hongtao; Liu, Yingru; Hou, Mingyu; Yang, Xinlei; Mu, Guojun; Liu, Lifeng (Frontiers in Genetics, 2021)
Drought is one of the major abiotic stress factors limiting peanut production. It causes the loss of pod yield during the pod formation stage. Here, one previously identified drought-tolerant cultivar ‘L422’ of peanut, was stressed by drought (35%±5%) at pod formation stage for 5, 7 and 9 days. To analyze the drought effects on peanut, we conducted physiological and transcriptome analysis in leaves under well-watered (CK1, CK2 and CK3) and drought-stress conditions (T1, T2 and T3). By transcriptome analysis, 3,586, 6,730 and 8,054 differentially expressed genes (DEGs) were identified in ‘L422’ at 5 days (CK1-vs-T1), 7 days (CK2-vs-T2), and 9 days (CK3-vs-T3) of drought stress, respectively, and 2846 genes were common DEGs among the three-time points. Furthermore, the result of weighted gene co-expression network analysis (WGCNA) revealed one significant module that was close correlation with drought stress and physiological data. A total of 1,313 significantly up-/down-regulated genes, including 61 transcription factors, were identified in the module at three-time points throughout the drought stress stage. Additionally, six vital metabolic pathways, namely, ‘MAPK signaling pathway-plant’, ‘flavonoid biosynthesis’, ‘starch and sucrose metabolism’, ‘phenylpropanoid biosynthesis’, ‘glutathione metabolism’, and ‘plant hormone signal transduction’ were enriched in ‘L422’ under severe drought stress. Nine genes responding to drought tolerance were selected for quantitative real-time PCR (qRT-PCR) verification and the results agreed with transcriptional profile data, which revealing the reliability and accuracy of transcriptome data. Taken together, these findings could lead to a better understanding of drought tolerance and facilitate the breeding of drought-resistant peanut cultivars.